Tawḥīd Ḥākimiyyah Verses In Ibn ‘Āshūr’s Interpretation - Saifuddin Herlambang Munthe (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This paper discusses Ibn 'Āshūr's interpretation of the verses which serve as the basis of the Tawḥīd ḥākimiyyah concept. Despitebeing an expert in Islamic law, Ibn ‘Āshūr did not perceive the Tawḥīd ḥākimiyyah verses as a basis for the necessity to apply Shari'a law at the level of government. Perhaps the thought of